2022
DOI: 10.1093/infdis/jiac364
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Analyses in Highly Treatment-Experienced People With Human Immunodeficiency Virus (HIV) Treated With the Novel Capsid HIV Inhibitor Lenacapavir

Abstract: Background Lenacapavir is a first-in-class inhibitor of HIV-1 capsid function in clinical development for the treatment of heavily treatment-experienced (HTE) people with HIV (PWH) harboring multidrug resistance (MDR) in combination with an optimized background regimen (OBR). Here we describe resistance analyses conducted in the pivotal phase 2/3 CAPELLA study. Methods CAPELLA enrolled viremic HTE PWH with resistance to ≥ 3 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 12 publications
0
42
0
Order By: Relevance
“…Extensive decoration of the PF74 skeleton by Gilead Sciences generated lenacapavir (LEN; GS-6207), which has picomolar anti-HIV-1 activity (EC 50 = 105 pM), favorable metabolic stability, and is approved by the European Community (EC) [ 27 ]. Nevertheless, limited by its complicated structure and labor-intensive synthesis, LEN displays extremely poor water solubility, resulting in mainly injectable use, and drug-resistant strains have also already appeared in clinical trials [ 28 ]. Further structural optimization of PF74 to identify novel CA modulators is needed to address these inadequacies.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive decoration of the PF74 skeleton by Gilead Sciences generated lenacapavir (LEN; GS-6207), which has picomolar anti-HIV-1 activity (EC 50 = 105 pM), favorable metabolic stability, and is approved by the European Community (EC) [ 27 ]. Nevertheless, limited by its complicated structure and labor-intensive synthesis, LEN displays extremely poor water solubility, resulting in mainly injectable use, and drug-resistant strains have also already appeared in clinical trials [ 28 ]. Further structural optimization of PF74 to identify novel CA modulators is needed to address these inadequacies.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the capsid inhibitor lenacapavir (LEN) is administered subcutaneously (sc) every six months. The recent CALIBRATE trial showed the non-inferiority of sc LEN, combined with two oral daily ARV, in ARV-naïve patients [ 1 ], and the CAPELLA trial showed a high percentage of virological response of LEN in combination with an optimized background regimen; in patients with virological failure and multidrug-resistant viruses, 86% of them achieved a plasma viral load < 200 c/mL at week 52 [ 2 ]. The NNRTI rilpivirine (RPV) and the integrase strand-transfer inhibitor (INSTI) cabotegravir (CAB) have also been developed in a long-acting form.…”
Section: Future Of Antiretroviral Drugs: What To Expect?mentioning
confidence: 99%
“…Indeed, protease inhibitors mutations can be accompanied by selection of mutations in the gag cleavage sites. Resistance analyses performed in the randomized controlled phase 3 trials showed the emergence of resistance mutations in case of VF in 2/157 patients in the CALIBRATE trial, including ARV-naïve patients, and in 8/72 in the CAPELLA trial including patients with MDR viruses [ 1 , 2 ]. These data suggest a low genetic barrier to resistance of LEN, and a 2nd generation of capsid inhibitors will probably be needed to improve genetic barrier to resistance.…”
Section: Evolution Of Arv Drug Resistancementioning
confidence: 99%
“…Despite PF74’s unique antiviral profiles, its poor antiviral activity (EC 50 = 0.87 μM, MT-4 cells) and metabolic instability have hindered further studies . Lenacapavir (LEN, Figure ), a multi-round iterative modification of PF74 by Gilead Science, has picomolar-level anti-HIV activity (EC 50 = 105 pM, MT-4 cells) and excellent metabolic stability and is the first FDA-approved HIV-1 CA inhibitor. , However, resistant strains insensitive to LEN have emerged during clinical trials and in vitro screening, and its complex synthesis and high administration costs have limited its clinical application. , Therefore, the challenge remains to discover new structural types of HIV-1 CA modulators that can be seamlessly integrated into current cART regimens.…”
Section: Introductionmentioning
confidence: 99%